Evaluasi Risiko Iklim Wilayah Tembakau di Kabupaten Temanggung - Tommy Harianto; Tania June; . Perdinan (Institut Pertanian Bogor, 2019)
Tobacco is one of the important commodities that becomes an income source for farmers as well as Original Local Government Revenue of Temanggung Districts. Unfortunately, in the last few decades the failure of tobacco harvest due to climate variability was often occurred. The decrease in both quality and quantity due to rainfall irregularities has caused tobacco farmers get decrease in income. This study aims to find out the climate profile besides impact and risk analysis of climate on tobacco in Temanggung District. Methods used in this study were Polygon Thiessen to find out the rainfall patterns in Temanggung District, and Probability Density Function to find out the conditions of rainfall change in each sub-district. Furthermore, the relationship between rainfall anomaly and temperature with tobacco productivity was analyzed using linear regression and t-test methods. The rainfall influence showed a negative correlation with tobacco productivity with coeffiicients of correlation and determination of r = -0.38 and R2 = 0.14, respectively, while the average temperature and maximum monthly temperature had a negative and significant effect on tobacco productivity. Rainfall anomaly in all sub-districts of Temanggung District showed a negative correlation with and affected tobacco productivity during June-September that was the phase of tobacco harvest. The effect of rainfall and temperature on tobacco productivity in Temanggung District needs to be a concern for local governments and tobacco farmers in efforts for adaptation and mitigation processes.